Digital Media Usage Behavior and Digital Media Marketing Factors Influencing Cultural Tourism Decision-Making of Tourists in Sriracha District, Chonburi Province. - Baibua, Naphattharakarn; Pruksorranan, Natthakan (Mahachula Academic Journal, 2025)
The study aims to examine the behavior of digital media usage, digital marketing media factors, and the decision-making process for cultural tourism among tourists in Sriracha District, Chonburi Province. It seeks to analyze the relationship between digital media usage behavior and digital marketing media factors that influence decisions to engage in cultural tourism in the specified area. This research employs a quantitative approach. The population and sample group for the study include 400 Thai tourists participating in cultural tourism in Sriracha District, Chonburi Province. The sampling method used is accidental sampling, with questionnaires as the data collection tool. Statistical analyses include percentage, mean, standard deviation, one-way ANOVA, and multiple regression analysis, with a significance level set at 0.05. The results revealed that 1) Digital media usage behavior and digital marketing media factors significantly influence the decision to participate in cultural tourism in Sriracha District, Chonburi Province. Most tourists use digital media for approximately 5–8 hours per day, especially between 12:01 PM and 3:00 PM, to evaluate options for purchasing tourism-related products and services. And 2) Differences in tourists’ digital media usage behavior significantly impact their decision to choose cultural tourism destinations. Statistically significant factors include the purpose of using media, the devices used, types of media, and types of content. Digital marketing media factors—such as advertising, public relations, personal selling, sales promotion, and direct marketing—significantly affect the decision-making process for cultural tourism in the area at a significance level of 0.05